The Year-End LIFO Purchase Decision: The Case of Farmer Brothers Company. - Barrett, M. Edgar; Bowen, Robert M.; Pfeiffer, Glenn M. (The Accounting Review, 1989)
ABSTRACT: Companies that use commodities as inputs (e.g., crude oil and coffee) often face inventory decisions in an environment of widely fluctuating prices. Under LIFO, the end-of-period decision to replace liquidated LIFO layers (or not) may dramatically affect cost of goods sold for both tax and financial reporting. In this paper, we first model the factors involved in the end-of-period decision to acquire inventory. We then apply this model in the context of the difficult situation faced by the management of the Farmer Brothers (coffee) Company in fiscal year 1977. The events reflected in Farmers Brothers' fiscal year 1977 financial statements reveal many of the economic factors involved in managing inventories recorded on a LIFO basis. The actual end-of-period decision reached by Company management is compared to plausible alternative actions. The analysis focuses on estimates of the effects of these alternative actions on cash flows and reported income as well as other factors that might have influenced management to increase the level of ending inventory in the face of declining prices.